Comparison of diosgenin related gene expression and content on organs of Trigonella foenum-graecum L. - Do Yeon Kwon; Sang Un Park (한국응용생명화학회, 2019)
Diosgenin is belong to the group of triterpenes that is a naturally major bioactive occurring steroid sapogenin and present in Dioscorea species (yams), fenugreek and Cotus sepciosus etc. This compound used pharmaceutical industry as the main precursor such as anti-inflammatory, lipid metabolism and anti-diabetes that is main bioactive chemical in Fenugreek. In order to compare diosgenin contents, different organs of fenugreek harvested, were examined in this study. Different organs (the flowers, stems, young leaves, mature leaves, roots and pods) were prepared, and the gene expression related diiosgenin and diosgenin accumulation were analyzed. Gene epxression shown highest in flower and then followed roots. In case of pod, all gene expression were shown very low. The highest accumulation was in young leave (2.05 mg/g), followed flower (0.79 mg/g), mature leave (0.79 mg/g) and pod (0.71 mg/g) that the most accumulated organ and the next organ were more than half. The lowest content level was in stem (0.17 mg/g) and root (0.4 mg/g).
Keywords: Trigonella foeunum-graecum L.; Diosgenin; qRT-PCR; HPLC